The benefits of practice Muay Thai on quality of life: a female perspective (Research, Society and Development, 2023)
Quality of life. Muay Thai represents a martial art that optimizes physical conditioning and stimulates psychosocial development through its ideology. Therefore, it provides its practitioners with benefits in the various spheres that involve the promotion of quality of life. Currently, there is a strong interest of the female public in practicing this sport in search of health and well-being promotion. Thus, the objective is to investigate and understand the benefits achieved through the practice of Muay Thai in the quality of life of the female population. A descriptive, exploratory cross-sectional research with a quantitative and qualitative approach was carried out in order to collect data on the subject. The results analyzed in this study were collected from a sample composed of women who practice this fight in a Muay Thai gym in Minas Gerais. In this context, two questionnaires were applied, one of their own authorship and the WHOQOL-bref, in an attempt to elucidate these objectives. After the discussion, it becomes evident that Muay Thai represents a tool capable of providing, in an integral way, these aspects of maintaining good health to women, involving biopsychosocial aspects.